2006
DOI: 10.1021/nl061253e
|View full text |Cite
|
Sign up to set email alerts
|

Composite-Hydroxide-Mediated Approach for the Synthesis of Nanostructures of Complex Functional-Oxides

Abstract: We demonstrate a generic approach for the synthesis of single-crystal complex oxide nanostructures of various structure types, such as perovskites, spinels, monoclinic, corundum, CaF 2 structured, tetragonal, and even metal hydroxides. The method is based on a reaction between a metallic salt and a metallic oxide in a solution of composite-hydroxide eutectic at ∼200°C and normal atmosphere without using an organic dispersant or capping agent. The synthesis technique is cost-effective, one-step, easy to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(166 citation statements)
references
References 33 publications
4
162
0
Order By: Relevance
“…Besides the syn thesis of conventional binary oxides (discussed by J. Wang et al in this issue), methods have been developed to synthesize NWs of functional and smart ma terials. Liu et al 41 have demonstrated a generic approach for the synthesis of single -crystal complex oxide nanostructures of perovskites, spinels, and various hydroxides, including monoclinic, corundum, CaF 2 -struc tured, tetragonal, and metal hydroxides. 42,43 The method is based on a reaction between a metallic salt and a metallic oxide in a solution of composite hydroxide eutectic at ϳ200ЊC and 1 atm without using an organic dispersant or capping agent.…”
Section: Nanowires Of Functional and Smart Materialsmentioning
confidence: 99%
“…Besides the syn thesis of conventional binary oxides (discussed by J. Wang et al in this issue), methods have been developed to synthesize NWs of functional and smart ma terials. Liu et al 41 have demonstrated a generic approach for the synthesis of single -crystal complex oxide nanostructures of perovskites, spinels, and various hydroxides, including monoclinic, corundum, CaF 2 -struc tured, tetragonal, and metal hydroxides. 42,43 The method is based on a reaction between a metallic salt and a metallic oxide in a solution of composite hydroxide eutectic at ϳ200ЊC and 1 atm without using an organic dispersant or capping agent.…”
Section: Nanowires Of Functional and Smart Materialsmentioning
confidence: 99%
“…Several chemical methods have been developed for the low-temperature preparation of micro-and nano-sized perovskite crystals such as molten salt synthesis [9][10], solvothermal and hydrothermal method [11][12][13][14][15][16][17], decomposition of bimetallic alkoxide precursors [18][19][20], microwave route [21][22][23][24], and biosynthesis [25]. Though these routes offer successful synthesis of perovskite nanoparticles with high quality and good crystalline, they usually require temperatures higher than 100°C or expensive reactants.…”
Section: Introductionmentioning
confidence: 99%
“…The Ba-doped CeO 2 is synthesized through the newly invented nanomaterial fabrication route of the CHM method [11][12][13][14][15]. In a typical reaction, a 9 g amount of mixed NaOH and KOH with a Na/K ratio of 51.5:48.5 is placed in a 25 ml covered Teflon vessel.…”
Section: Methodsmentioning
confidence: 99%